2011
DOI: 10.1007/s10792-011-9447-7
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and functional correlation of frequency-doubling technology perimetry (FDTP) in multiple sclerosis

Abstract: To study the correlation between the results of frequency-doubling technology perimetry (FDTP), visual function (visual acuity, contrast vision, standard automated perimetry (SAP)) and the thickness of the retinal nerve fiber layer (RNFL) throughout the course of multiple sclerosis (MS). Sixty-six eyes of thirty-three patients suffering from MS were chosen. Thirty-five eyes had a previous history of optic neuritis (ON group) and thirty-one eyes had no previous history of optic neuritis (non-ON group). The FDTP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
5
0
1
Order By: Relevance
“…To the best of our knowledge, this is the first study evaluating the correlation between BMO and different areas of the visual field during demyelinating diseases. A high correlation was found, as for RNFL and GCL in similar studies of patients with and without a history of ON (37,38). Essentially studied during glaucoma neuropathy, the correlation between BMO and MD is at least close to or sometimes better than the RNFL.…”
Section: Discussionsupporting
confidence: 54%
“…To the best of our knowledge, this is the first study evaluating the correlation between BMO and different areas of the visual field during demyelinating diseases. A high correlation was found, as for RNFL and GCL in similar studies of patients with and without a history of ON (37,38). Essentially studied during glaucoma neuropathy, the correlation between BMO and MD is at least close to or sometimes better than the RNFL.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, an RNFL below 75 μm was significantly correlated with visual field defects. It has been observed that despite the fact that visual acuity returned to normal after optic neuritis, patients still complain of subjective decreased vision, which may result from decreased contrast sensitivity or visual field defects [21, 31, 34]. …”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that about 15–20 % of patients with multiple sclerosis are diagnosed with optic neuritis in the course of the disease [1, 20]. There are articles suggesting that this proportion is much higher and may be as high as 50 % [1, 21, 22]. The main symptoms include: subacute, unilateral, and decreased visual acuity, which may be accompanied by dyschromatopsy, decreased contrast sensitivity, phosphenes (positive visual phenomena) seen as white or colorful flashes, as well as ocular pain or pain around the eyeball, which increases with eye movement and afferent pupillary defect.…”
Section: Introductionmentioning
confidence: 99%
“…48 Visual field sensitivity (as measured by the mean deviation (MD) from age-matched normal values) is reduced in MS patients relative to normal subjects, with the greatest reduction being observed in those eyes with a history of ON. 49,50 Mean deviation is correlated with TD-OCT-derived RNFL thickness in MS eyes with a history of ON, 51,52 although the quantitative relationship with deeper retinal layers remains unstudied. Given that MS patients are prone to fatigue 53 and the adverse effects of fatigue on both visual sensitivity and reliability when performing perimetry, 48 more objective measures of visual function (such as electrophysiology) are likely to be helpful when assessing MS patients.…”
Section: Relationship Of Oct Parameters With Clinical Outcome Measuresmentioning
confidence: 99%